Hamimaera hamigera Haswell 1879 - Hughes, Lauren E. (Zenodo, 2016)
Hamimaera hamigera (Haswell, 1879b) Moera hamigera Haswell, 1879b: 333, pl. 21, fig. 1. Maera hamigera .— Stebbing, 1888: 1790.— Della Valle, 1893: 723.— Stebbing 1906: 437.— Barnard & Barnard, 1983: 623.—? Ren, 2012: 240 –242, fig. 104. Linguimaera hamigera .— Lowry & Springthorpe, 2005: 249 –252, figs. 11–13. Hamimaera hamigera .— Krapp-Schickel, 2008: 29 –30, fig. 27. not Maera hamigera .— Walker 1909: 335, pl. 43, fig. 5, pl. 3.— Karaman & Ruffo, 1971: 152, figs 21–23.— Lyons & Myers, 1993: 587, fig. 10. (= L. caesaris Krapp-Schickel, 2003) not Maera hamigera .— Stebbing 1910a: 600.— K.H. Barnard, 1916: 196, pl. 27, figs 11–12.— Chilton, 1921: 73.— J.L. Barnard, 1965: 507, fig. 16 (in part).— Ledoyer, 1983: 523, figs 196–197.— Karaman, 1982: 312, fig. 211.— Myers, 1997: 109.— Appadoo, Myers & Fagoonee, 2002: 664 –668, figs 14–16. Material examined. New South Wales: 2 specimens, AM P.77036, Surgeons Reef, north of North West Solitary Island (30°00′27″S 153°16′13″E), 10–11 m, orange sponge, 30 April 2005, coll. P.B. Berents (NSW 2790); 3 specimens, AM P.77035, Chopper Rock, northwest of North West Solitary Island (30°00′30″S 153°15′22″E), 17 m, ascidian Herdmania momus , 29 April 2005, coll. S.J. Keable (NSW 2778); 3 specimens, AM P.77009, Black Rocks, south of Smoky Cape (30°56′59″S 153°04′29″E), 10.3 m, reef rock encrusted with red and green algal turf, 10 February 2002, coll. S.J. Keable (NSW 1814); 6 specimens, AM P.77012, Black Rock, south of Smoky Cape (30°56′58″S 153°04′32″E), 10 m, reef rock, 13 February 2002, coll. S.J. Keable (NSW 1867); 1 specimen, AM P.77021, north west corner of Green Island, north of Smoky Cape (30°54′41″S 153°05′18″E), 8–10 m, ascidians covered with algae and encrustations, 15 February 2002, coll. R.T. Springthorpe (NSW 1923); 2 specimens, AM P.77016, northwest corner of Green Island, north of Smoky Cape (30°54′41″S 153°05′18″E), 11 m, tunicates and sponge, 15 February 2002, coll. S.J. Keable (NSW 1914); 2 juvenile specimens, AM P.97858, north west corner of ...